WAYS TO SIMPLIFY AND DIGITALIZE THE ACCOUNTING SYSTEM IN THE CONTEXT OF AN INNOVATIVE ECONOMY - Siroj, Zarina Rustambekovna (THE INNOVATION ECONOMY, 2026)
This article analyzes current issues of simplifying and digitalizing accounting systems in the context of an innovative economy. It examines the benefits of implementing modern information technologies, including cloud platforms, automated accounting systems, and artificial intelligence-based solutions, in the process of digital transformation. It also provides a scientifically substantiated approach to improving accounting systems by implementing reporting based on international standards, ensuring data transparency, and reducing the influence of human error.